Eighteen-month clinical performance of composite resin restorations with two different adhesive systems for molars affected by molar incisor hypomineralization - de Souza, Juliana Feltrin; Fragelli, Camila Bullio [UNESP]; Jeremias, Fabiano [UNESP]; Paschoal, Marco Aurélio Benini; Santos-Pinto, Lourdes [UNESP]; de Cássia Loiola Cordeiro, Rita [UNESP] (Springer Nature, 2017)
Introduction: The restorative management of molars with molar incisor hypomineralization (MIH) represents a challenge in the clinical practice with high failure rate. Objective: The aim of this study is to evaluate the clinical survival of direct composite resin restorations in first permanent molars (FPMs) that are affected by MIH, comparing two adhesive systems. Material and methods: We selected 41 FPMs with MIH from children aged 6–8 years. FPM fully erupted and with restorative treatment needed were the inclusion criteria. We excluded FPMs with destroyed crowns. The FPMs were randomly assigned to two groups: self-etching adhesive (SEA) and total-etch adhesive (TEA). Clinical evaluation was performed by a blinded examiner during 18 months according to the modified US Public Health Service (USPHS) criteria. The actuarial method was used to evaluate survival of the restorations, and Chi-square and Fisher’s exact tests were used to compare differences between the groups (α = 5 %). Results: The cumulative survival rates were 100 % at 1 month, 89 % at 6 months, 73 % at 12 months, and 68 % at 18 months in SEA, and 95 % at 1 month, 72 % at 6 months, 59 % at 12 months, and 54 % at 18 months in TEA; there was no significant difference between groups. Conclusions: There was no difference in clinical survival of restorations in FPMs affected by MIH using TEA or SEA adhesives in the end of 18 months. Clinical relevance: It was suggested that SEAs as well as TEAs can be applied to restore molars affected by MIH, when it is performed a conservative cavity preparation. Once, cavosurface margins (cavity design) in hypomineralized enamel have less bonding capability.
Keywords: Adhesive system; Dental restoration; Molar incisor hypomineralization; Randomized clinical trial; Treatment